2018
DOI: 10.1371/journal.pone.0204243
|View full text |Cite
|
Sign up to set email alerts
|

Major ampullate silk gland transcriptomes and fibre proteomes of the golden orb-weavers, Nephila plumipes and Nephila pilipes (Araneae: Nephilidae)

Abstract: Natural spider silk is one of the world’s toughest proteinaceous materials, yet a truly biomimetic spider silk is elusive even after several decades of intense focus. In this study, Next-Generation Sequencing was utilised to produce transcriptomes of the major ampullate gland of two Australian golden orb-weavers, Nephila plumipes and Nephila pilipes, in order to identify highly expressed predicted proteins that may co-factor in the construction of the final polymer. Furthermore, proteomics was performed by liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…The number of reported proteins is broadly similar to that found by Aparecido dos Santos et al (2019 and Whaite et al (2018) in which three major ampullate spidroins, one minor ampullate spidroin, and one tubuliform spidroin were identified in T. clavipes . Similarly, Aparecido dos Santos‐Pinto et al (2019) and Whaite et al (2018) identified spidroins homologous to the proteins MaSp‐c, MaSp‐d, MaSp‐g, and MaSp‐h, and to the proteins MiSp‐a and MiSp‐d (following the labeling by Babb et al, 2017), in the species T. plumipes and Nephila pilipes .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The number of reported proteins is broadly similar to that found by Aparecido dos Santos et al (2019 and Whaite et al (2018) in which three major ampullate spidroins, one minor ampullate spidroin, and one tubuliform spidroin were identified in T. clavipes . Similarly, Aparecido dos Santos‐Pinto et al (2019) and Whaite et al (2018) identified spidroins homologous to the proteins MaSp‐c, MaSp‐d, MaSp‐g, and MaSp‐h, and to the proteins MiSp‐a and MiSp‐d (following the labeling by Babb et al, 2017), in the species T. plumipes and Nephila pilipes .…”
Section: Discussionsupporting
confidence: 85%
“…Unveiling the principles of the spinning process requires a combined effort from different research fields, including genomics, proteomics, and materials science. Thus, proteomics studies (Aparecido dos Santos‐Pinto et al, 2019; Whaite et al, 2018) identified the presence of a numerous set of proteins in each of the spinning glands that can be grouped in six subsets whose functions range from housekeeping proteins to proteins related to the folding and modification of spidroins (Aparecido dos Santos‐Pinto et al, 2015). Needless to say, the characterization of the subset that comprises the structural proteins with which the fibers are generated, the spidroin proteins, is especially relevant to understand the microstructure and properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…3 ). We identified sequences belonging to the seven major spidroin clades (aciniform, aggregate, flagelliform, major ampullate, minor ampullate, piriform, and tubuliform), as well as three uncharacterized spidroins with homology to genes that had previously been identified only in the orb-weaving genus Trichonephila (Sp-5803, Sp-907/74867, and Sp-1339) [ 14 , 38 ]. Phylogenetic conflict can occur between spidroin N- and C-termini, and N-termini generally contain more phylogenetic signal [ 21 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…One spidroin, Sp-907/ Sp-74867, was more highly expressed in Spiny Legs. Many of the remaining DE genes (both up-and downregulated) belong to groups of genes previously identified as having silk gland-specific expression (in [18,38,40]), including proteases, transferases, and genes associated with cellular transport and secretion; the where not labelled, support values are 100%. Branches leading to species sequenced in this study are colored red, and Spiny Leg species are labelled with blue text.…”
Section: Differential Expression Analysis and Gene Ontology Enrichmentmentioning
confidence: 99%
“…A foremost example in structural proteins is proline hydroxylation in collagen; without this PTM the procollagen strands cannot achieve their characteristic triple-helix structure. 39 Within spider silk, little is known about the exact role and structural impact of PTMs; 40 however, both MaSp1 and MaSp2 have been shown to carry phosphorylated serine and tyrosine residues within the repetitive region. 41 , 42 The position and enhancement of negative charge associated with the phosphorylation has known impacts on formation of helical structures in other proteins and show similar patterns in spider silk with a molecular model of MaSp1 incorporating phosphorylate serine and tyrosine showing increased coil formation with greater formation of alpha helices and a reduction of the amount of 3 10 helices than in previous models.…”
Section: Complex Composition Of Spider Dragline Silkmentioning
confidence: 99%